2008
DOI: 10.1016/j.ymgme.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

A humanized mouse model for the reduced folate carrier

Abstract: The ubiquitously expressed reduced folate carrier (RFC) or SLC19A1 is recognized to be an essential transport system for folates in mammalian cells and tissues. In addition to its generalized role as a folate transporter, RFC provides specialized tissue functions including absorption across intestinal/ colonic epithelia, transport across the basolateral membrane of renal proximal tubules, transplacental transport of folates, and folate transport across the blood-brain barrier. The human RFC (hRFC) gene is regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…While there have been extensive studies of high frequency sequence polymorphisms in the hRFC coding and noncoding regions in relation to a variety of pathological states (4,56), these associations remain controversial. The recent production of a “humanized” RFC mouse in which the mouse RFC gene is functionally replaced by the hRFC gene locus (198) holds promise for extending in vitro findings of hRFC regulation and function including polymorphic hRFC gene variants to a clinically relevant in vivo model. This will allow correlations with dietary folate status and biological manifestations of folate deficiency.…”
Section: 0 Research In Progress and Outstanding Research Questionsmentioning
confidence: 99%
“…While there have been extensive studies of high frequency sequence polymorphisms in the hRFC coding and noncoding regions in relation to a variety of pathological states (4,56), these associations remain controversial. The recent production of a “humanized” RFC mouse in which the mouse RFC gene is functionally replaced by the hRFC gene locus (198) holds promise for extending in vitro findings of hRFC regulation and function including polymorphic hRFC gene variants to a clinically relevant in vivo model. This will allow correlations with dietary folate status and biological manifestations of folate deficiency.…”
Section: 0 Research In Progress and Outstanding Research Questionsmentioning
confidence: 99%
“…This question can be restated on a molecular level as: are human genes expressed in mice regulated as if they are mouse genes or as if they are human genes. Evidence from some experiments with individual genes, for example, CBS and RFC, suggests that in terms of tissue speciWcity at least, human genes introduced into transgenic mice using large genomic DNA inserts are regulated diVerently from the cognate mouse genes and show tissue speciWcity similar to that seen in humans (Butler et al 2006;Patterson et al 2008). In an attempt to address this question more globally, Wilson et al (2008) studied mouse hepatocytes from Tc1 mice and relevant controls and concluded that genetic sequences on HSA21 largely determined the expression patterns of 121 HSA21 genes, with interspecies diVerences between mouse and human playing a secondary role.…”
Section: Mouse Models and The Study Of Dsmentioning
confidence: 99%
“…A humanized mouse model for the reduced-function folate carrier has been created [15]. Expressing human SLC19A1 in transport-deficient Chinese hamster ovary cells results in restoration of MTX transport and MTX sensitivity [4].…”
Section: Slc19a1 Pharmacogenomics Summarymentioning
confidence: 99%